Peningkatan Kemampuan Berhitung Dasar Anak Usia 3-4 TahunMelalui Media Kincir Angka - Elfia Aprimel Yanti; Susi Herlinda; Herwina Herwina (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to determine the basic counting ability of children aged 3–4 years through the use of number wheel media at KB Tunas Pertiwi Pejajaran. The method used is Classroom Action Research with a total of 15 children in one class as the research subjects. The results show that the use of number wheel media can improve children's basic counting ability, as indicated by the increase in the average class percentage from 35% in the initial condition to 50.56% in Cycle I, and significantly to 81.67% in Cycle II. This study provides an alternative learning medium in the form of a number wheel that is effective in improving early childhood basic counting skills, as well as enriching innovative and engaging learning strategies in the development of children's cognitive abilities.